2022
DOI: 10.1002/advs.202200986
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy‐Assembled Dual Probiotics System Ameliorates Cholestatic Drug‐Induced Liver Injury via Gut‐Liver Axis Modulation

Abstract: Cholestatic drug‐induced liver injury (DILI) induced by drugs or other xenobiotics is a severe and even fatal clinical syndrome. Here, living materials of hierarchy‐assembled dual probiotics system are fabricated by sequentially encapsulating probiotic Lactobacillus delbrueckii subsp. bulgaricus (LDB) and Lactobacillus rhamnosus GG (LGG) into Ca2+‐complexed polymer microspheres for effective prevention of cholestatic DILI. Upon entering intestinal tract of the constructed living materials, LGG is released beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…NCC could significantly increase the relative abundances of Lactobacillus , Prevotellaceae_UCG-001 , and Anaerotruncus , which would affect the levels of SCFAs, farnesoid X receptor (FXR) pathways, Takeda G-protein-coupled receptor 5 (TGR5) pathways, glucose homeostasis, fermentation capacity of gut microbiota, and intestinal motility. Lactobacillus could promote intestinal motility by increasing the contents of butyric acid and acetic acid and regulate bile acids, lipid, and glucose homeostasis by activating FXR and TGR5 signaling pathway. Prevotellaceae_UCG-001 and Anaerotruncus could increase the content of butyric acid, regulate glucose homeostasis by participating in glucose metabolism, and make the fermentation capacity of gut microbiota toward the benefit of the host. , …”
Section: Resultsmentioning
confidence: 99%
“…NCC could significantly increase the relative abundances of Lactobacillus , Prevotellaceae_UCG-001 , and Anaerotruncus , which would affect the levels of SCFAs, farnesoid X receptor (FXR) pathways, Takeda G-protein-coupled receptor 5 (TGR5) pathways, glucose homeostasis, fermentation capacity of gut microbiota, and intestinal motility. Lactobacillus could promote intestinal motility by increasing the contents of butyric acid and acetic acid and regulate bile acids, lipid, and glucose homeostasis by activating FXR and TGR5 signaling pathway. Prevotellaceae_UCG-001 and Anaerotruncus could increase the content of butyric acid, regulate glucose homeostasis by participating in glucose metabolism, and make the fermentation capacity of gut microbiota toward the benefit of the host. , …”
Section: Resultsmentioning
confidence: 99%
“… 48 Bile acid secretion is stimulated by similar mechanisms in a mouse model of drug-induced cholestasis by L. rhamnosus GG and other probiotic bacteria. 49 Although a causal relationship between decreased BSH activity and neonatal cholestasis remains unknown, BSH-based probiotic therapy is an intriguing potential therapeutic avenue. It is notable that our cholestatic neonates were on total parenteral nutrition for a longer duration of time than the control cohort and that half of the cholestatic infants developed NEC (2/6 patients required surgery).…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that LGG treatment helps alleviate ICP and cholestatic liver injury, which can be a potential therapeutic strategy for ICP. Chen et al 16 further demonstrated the great potential of LGG to alleviate cholestasis in mice model of cholestasis induced by α-naphthylisothiocyanate (ANIT) and clinical antiepileptic drugs valproate acid (VPA).…”
Section: Probiotics and Cholestasismentioning
confidence: 99%
“… 9 , 15 In some recent studies, the beneficial effects of probiotics on cholestasis have also been demonstrated. 16 , 17 Therefore, we reviewed the triangular relationship among gut microbiota, BA and cholestasis, revealing the potential role and possible mechanism of probiotics in the treatment of cholestasis.…”
Section: Introductionmentioning
confidence: 99%